TopClosure® tension-relief system for immediate primary abdominal defect repair in an adult patient with bladder exstrophy. Issue 1 (January 2020) - Zhu, Zhanyong; Tong, Yilan; Wu, Tianpeng; Zhao, Yueqiang; Yu, Mosheng; Topaz, Moris
Bladder exstrophy during adulthood is a rare deformity. A major surgical challenge encountered in bladder exstrophy cases is the repair of an anterior abdominal wall defect. The TopClosure® tension-relief system (TRS) is a simple and practical skin stretching and wound closure-secure system that can be useful in treating patients with bladder exstrophy. A 61-year-old man presented with a congenital bladder valgus and epispadias. The dorsal side of the penis was split. The patient underwent valgus cystectomy, bilateral ureteral skin stoma creation, and primary closure of the large defect of the anterior abdominal wall using the TopClosure® TRS. At the 1-year follow-up after surgery, the patient had recovered well, and there were no indications of major complications. Utilization of the TopClosure® TRS to repair the large abdominal defect is an innovative method for abdominal reconstruction. The TopClosure® TRS reduces operative time and the duration of hospital stay and improves wound aesthetics.